2018
DOI: 10.1101/gr.231506.117
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between alternative polyadenylation and miRNAs in the regulation of protein translational efficiency

Abstract: 3' UTRs play important roles in the gene regulation network via their influence on mRNA stability, translational efficiency, and subcellular localization. For a given gene, 3' UTRs of different lengths generated by alternative polyadenylation (APA) may result in functional differences in regulation. The mechanistic details of how length changes of 3' UTRs alter gene function remain unclear. By combining APA sequencing and polysome profiling, we observed that mRNA isoforms with shorter 3' UTRs were bound with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 35 publications
(51 reference statements)
2
31
0
Order By: Relevance
“…In fact, a recent study has reported that in some cell lines, distal PAS usage resulting in lengthened 3′UTR decreases polysome occupancy and represses mRNA translation in comparison with shortened 3′UTR isoform. 108 Therefore, the impact of 3′UTR APA on mRNA translation may vary in a gene- and 3′UTR sequence-dependent manner. Further work is required to delineate how various cis elements affect the translation efficiency of APA isoforms in different conditions and different cell types.…”
Section: Molecular Effects Of Apamentioning
confidence: 99%
“…In fact, a recent study has reported that in some cell lines, distal PAS usage resulting in lengthened 3′UTR decreases polysome occupancy and represses mRNA translation in comparison with shortened 3′UTR isoform. 108 Therefore, the impact of 3′UTR APA on mRNA translation may vary in a gene- and 3′UTR sequence-dependent manner. Further work is required to delineate how various cis elements affect the translation efficiency of APA isoforms in different conditions and different cell types.…”
Section: Molecular Effects Of Apamentioning
confidence: 99%
“…In contrast to ribosome profiling, which determines the position of ribosomes within mRNA coding sequence, polysome profiling enables the analysis of entire mRNA transcripts. Consequently, this permits the study of individual transcript isoforms with particular resonance for the identification of conserved cis-acting sequences and structural motifs that can participate in transcript-specific translational regulation [18][19][20][21]. Furthermore, polysome profiling is readily combinable with several downstream applications, including microarrays and next generation sequencing (NGS) techniques, to identify polysome-bound mRNAs [16,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Curiously, VSV infection has also been reported to cause widespread shortening of host mRNA 3′UTR via alternative polyadenylation (X. Jia et al, 2017). The shortening events occurred more frequently in genes functioning in antiviral and interferon signaling suggest that such 3′UTR shortening is an integrated antiviral response, potentially to enhance the translation efficiency of the antiviral mRNAs via removal of miRNA‐binding site (Y. Fu et al, 2018; Mayr & Bartel, 2009). Our group has also reported that virus infection causes an alternative 5′UTR event that enhances the translation of the ciliopathy gene INPP5E, the expression of which inhibits HSV and VSV infection (Hoang et al, 2019).…”
Section: Emerging Translation Strategies During Virus–host Interactionmentioning
confidence: 99%